Experimental assessment of obsidian versus chert lanceolate projectile point durability and robusticity: Semi‐static fracture strength and dynamic impact. (17th May 2022) - Gala, Nicholas; Mika, Anna; Wilson, Michael; Williams, Jeremy; Buchanan, Briggs; Walker, Robert S.; Bebber, Michelle R.; Eren, Metin I.
Abstract: Stone‐tipped weaponry was important for the survival of past peoples, and many functional and non‐functional factors likely influenced their design. Two functional factors that past peoples likely considered in the design of their stone tips are durability (whether or not a stone tip breaks) and robusticity (how much damage is incurred upon breakage). Many factors have been shown experimentally to influence stone tip influence durability and robusticity, including stone raw material. Here, we further explore the relationship between stone raw material and stone tip durability and robusticity via controlled experiments comparing chert and obsidian. We first demonstrate with semi‐static fracture strength analyses that obsidian stone tips require less force to break than do chert stone tips. We then show with dynamic ballistics impact testing that obsidian stone tips are less durable and robust than chert stone tips. Our results are entirely consistent with previous experimental comparisons of chert versus obsidian stone tips, and support the hypothesis that past peoples, when presented with multiple raw materials, likely weighed their costs and benefits in the process of selection.